Draft Outline Fifth Five year Plan Assam Vol. III - Planning Commission (Planning Commission, 1973)
The Draft Outline of the Fifth Five-Year Plan for Assam (1973) presents a structured approach for socio-economic development in the state, addressing critical issues such as poverty, population growth, labor force dynamics, and income levels. The plan estimates that over half of Assam’s population lives below the poverty line, with urbanization and population growth projected to rise steadily. Strategies for employment generation focus on agriculture, irrigation, social services, and infrastructure, while investment requirements emphasize poverty alleviation and sectoral development. Regional cost disadvantages and fiscal disparities are acknowledged, highlighting the need for targeted interventions. Overall, the plan seeks to enhance living standards, stimulate economic growth, and ensure long-term socio-economic sustainability in Assam.
Planning and Development Department Government Of Assam June, 1973
Planning and Development Department Government Of Assam June, 1973
Keywords: Fifth Five-Year Plan; Assam; Poverty Estimates; Population Projections; Labor Force; Income Projections; Employment Generation; Investment Requirements; Price Levels; Infrastructure Development